Intervention studies to reduce the impact of climate change on health in rural communities in the United States: a systematic review - Daniel J Smith; Elizabeth Mizelle; Sharon L Leslie; Grace X Li; Sheila Stone; Peyton Stauffer; Anna Smith; Gianna Lewis; E Lola Rodden; Ruth McDermott-Levy; Lisa M Thompson (IOP Publishing, 2023)
Climate change, the greatest public health threat of the 21st century, will uniquely affect rural areas that are geographically isolated and experience greater health inequities. This systematic review describes and evaluates interventions to lessen the effects of climate change on human health in the rural United States, including interventions on air pollution, vector ecology, water quality, severe weather, extreme heat, allergens, and water and food supply. Searches were constructed based on the eight domains of the Centers for Disease Control and Prevention (CDC) Framework "Impact of Climate Change on Human Health." Searches were conducted in EBSCO Environment Complete, EBSCO GreenFILE, Embase.com, MEDLINE via PubMed, and Web of Science. Duplicate citations were removed, abstracts were screened for initial inclusion, and full texts were screened for final inclusion. Pertinent data were extracted and synthesized across the eight domains. Article quality was assessed using the Mixed Methods Appraisal Tool. Of 8471 studies screened, 297 were identified for full text review, and a total 49 studies were included in this review. Across the domains, 34 unique interventions addressed health outcomes due to air pollution ( n = 8), changes in vector ecology ( n = 6), water quality ( n = 5), severe weather ( n = 3), extreme heat ( n = 2) increasing allergens ( n = 1), water and food supply ( n = 1), and across multiple CDC domains ( n = 8). Participatory action research methodology was commonly used and strived to mobilize/empower communities to tackle climate change. Our review identified three randomized controlled trials, with two of these three published in the last five years. While original research on the impact of climate change on health has increased in the past decade, randomized control trials may not be ethical, cost effective, or feasible. There is a need for time-efficient and high-quality scholarship that investigates intervention efficacy and effectiveness for reducing health impacts of climate change upon rural populations.